Laparoscopic "Shaving" for infiltrative external adenomyosis of bowel muscularis and concomitant deep infiltrating endometriosis - Kuan- Lin Wu; Peng Teng Chua; Chyi- Long Le (Wolters Kluwer Medknow Publications, 2021)
Deep infiltrating endometriosis (DIE) is a common finding in patients diagnosed with adenomyosis. Women commonly present with severe, incapacitating dysmenorrhea. We report a case of severe dysmenorrhea and lower abdominal tightness for 4 years, diagnosed with posterior adenomyosis. The patient underwent surgery and DIE involving the rectosigmoid and coexisting uterocervical adenomyosis infiltrating bowel muscularis successfully diagnosed and treated using laparoscopic "shaving" technique. Dysmenorrhea significantly resolved after surgery. Laparoscopic surgical "shaving" technique for external adenomyosis infiltrating Rectosigmoid muscularis is feasible, where uterine preservation is desired.